Organizational Commitment as a Predictor of Teacher Kindergarten Performance in Implementation of ESDIGDC - Suparji Suparji (Humanistic Network for Science and Technology (HNST), 2017)
In order to achieve national development goals in the field of children health, the government is committed to enhancing the growth and development of children through the “Early Stimulation, Detection and Intervention for Growth and Development of Children (ESDIGDC)” Program. Efforts to improve the health status of children is very important, because in addition to being the target of health development, it also becomes an indicator of the health status of children is to prepare children to achieve optimal growth and development . This study aimed to analyze the influence of organizational commitment on the performance of kindergarten teacher in implementation of ESDIGDC Program. The subjects of this cross sectional study were 68 kindergarten teacher at Panekan Sub District, Magetan District, East Java Province, Indonesia. Data were collected through questionnaires and then analyzed using linear regression. The results showed that p-value = 0.001 (significant), so it could be concluded that there was the influence of organizational commitment on the performance of kindergarten teacher in implementation of ESDIGDC. Keywords: ESDIGDC, Kindergarten teacher, Organizational commitment, Performance